2016
DOI: 10.1149/2.0061701jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Imaging of Lithium Ion Battery Electrode Materials

Abstract: In this study we present a novel method of lithium ion battery electrode sample preparation with a new type of epoxy impregnation, brominated (Br) epoxy, which is introduced here for the first time for this purpose and found suitable for focused ion beam scanning electron microscope (FIB-SEM) tomography. The Br epoxy improves image contrast, which enables higher FIB-SEM resolution (3D imaging), which is amongst the highest ever reported for composite LFP cathodes using FIB-SEM. In turn it means that the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…261,262 For example, using phase contrast XCT and high-Z compound epoxy-impregnation techniques for FIBSEM, it is possible to achieve good contrast for carbon materials. 263,264 Another technique being utilized is to study the effects of mechanical compression on carbon-based electrodes. 170 Table 6 summarises the range of materials and compression conditions previously reported in the literature (non XCT-based).…”
Section: Quantification and Modelling Of Electrode Properties At Micrmentioning
confidence: 99%
“…261,262 For example, using phase contrast XCT and high-Z compound epoxy-impregnation techniques for FIBSEM, it is possible to achieve good contrast for carbon materials. 263,264 Another technique being utilized is to study the effects of mechanical compression on carbon-based electrodes. 170 Table 6 summarises the range of materials and compression conditions previously reported in the literature (non XCT-based).…”
Section: Quantification and Modelling Of Electrode Properties At Micrmentioning
confidence: 99%
“…This disconnect has resulted in a significant effort to develop mesoscale modeling and simulation capabilities within the battery modeling field. [16][17][18][19] Recent advancements in mesoscale imaging techniques have enabled detailed visualization of complex electrode mesostructures, [20][21][22][23][24][25][26][27][28][29][30][31][32] allowing modeling efforts to progress to real electrode morphologies. 20,27,[33][34][35][36][37][38][39][40][41][42] To bridge the gap between mesoscale and cell-level simulations, efforts have been made to extract electrode-scale properties from mesoscale reconstructions.…”
mentioning
confidence: 99%
“…Four isolated LTO secondary particles obtained using the absorption contrast imaging mode. (a) particle (1), (b) particle (2), (c) particle (3), (d) particle (4). The microstructure data for these particles are listed in Table III.…”
Section: Resultsmentioning
confidence: 99%
“…The high performance LIB requires high capacity active material and optimized electrode structure [1][2][3] which directly influence the overall cell performance such as rate capability, cycle life, and safety. [4][5][6] For example, using in-situ measurement of lithium transport Harris et al 6 showed the necessity for microstructural information to study lithium plating and dendrite growth in a graphite anode during the battery charging process.…”
mentioning
confidence: 99%